Sustainability Analysis of Beneficiaries of the Latrine Program Assistance in Pekon Negeri Ratu Ngabur - Ismail, M Rizky; Ardianti, Indah Marlina; Oktarina, Depi; Pawhestri, Suci Wulan (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2024)
Sustainable Development Goals (SDGs) are a global long-term program aimed at optimizing all potentials and resources possessed by each country. The latrine program is a derivative of the 6th SDG, which focuses on clean water and proper sanitation. Sanitation remains a public and global issue that still requires government attention. This research aims to analyze the achievement of the latrine program indicators in Pekon Negeri Ratu Ngambur and to understand the changes in healthy living behaviors among the community after the latrine program. This research employs a descriptive qualitative method with a sampling technique called purposive sampling, consisting of 17 samples, including 7 supporting samples and 10 core samples. Data collection involved document studies, interviews, observations, and documentation, with data management steps including data collection, data reduction, data presentation, data verification, and conclusion drawing. The research results show that 12 indicators of the healthy latrine program were achieved 70% overall, while 30% were not achieved. After the program was implemented by the village government, the community experienced improved cleanliness and comfort in their lives. The latrine sustainability provided by the village government to underprivileged residents is still being used in daily life, where economic factors also directly drive the sustainability of latrine development in terms of facility additions and improvements. The changes in healthy living behaviors among the community post-latrine program include greater concern for health and environmental cleanliness to prevent diseases like diarrhea. The ownership of latrines has successfully changed the community's behavior from open defecation to using healthy latrines, resulting in improved community health levels.AbstrakTujuan Pembangunan Berkelanjutan (SDGs) adalah program jangka panjang global yang bertujuan untuk mengoptimalkan semua potensi dan sumber daya yang dimiliki oleh setiap negara. Program jamban adalah turunan dari SDG ke-6, yang berfokus pada air bersih dan sanitasi yang layak. Sanitasi tetap menjadi isu publik dan global yang masih memerlukan perhatian pemerintah. Penelitian ini bertujuan untuk menganalisis pencapaian indikator program jamban di Pekon Negeri Ratu Ngambur dan memahami perubahan perilaku hidup sehat di kalangan masyarakat setelah adanya program jamban. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengambilan sampel purposive sampling, yang terdiri dari 17 sampel, termasuk 7 sampel pendukung dan 10 sampel inti. Pengumpulan data melibatkan studi dokumen, wawancara, observasi, dan dokumentasi, dengan langkah-langkah pengelolaan data meliputi pengumpulan data, reduksi data, penyajian data, verifikasi data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa 12 indikator program jamban sehat tercapai sebesar 70% secara keseluruhan, sementara 30% belum tercapai. Setelah program ini diterapkan oleh pemerintah desa, masyarakat merasakan peningkatan kebersihan dan kenyamanan dalam hidup mereka. Keberlanjutan jamban yang disediakan oleh pemerintah desa kepada warga kurang mampu masih digunakan dalam kehidupan sehari-hari, di mana faktor ekonomi juga secara langsung mendorong keberlanjutan pembangunan jamban dalam hal penambahan dan perbaikan fasilitas. Perubahan perilaku hidup sehat di masyarakat pasca-program jamban mencakup kepedulian yang lebih besar terhadap kesehatan dan kebersihan lingkungan untuk mencegah penyakit seperti diare. Kepemilikan jamban berhasil mengubah perilaku masyarakat dari buang air besar sembarangan menjadi menggunakan jamban sehat, yang berdampak pada peningkatan tingkat kesehatan masyarakat.